Pengaruh Artificial Intelligence dalam Pembuatan Laporan Keuangan - Resalia Resalia; Heni Nurmayana Soleha; Alya Bahira; Rudi Sanjaya (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The presence of Artificial Intelligence (AI) has a significant impact on the preparation of financial reports, especially in terms of efficiency and accuracy. This article aims to examine the influence of AI on the process of preparing financial reports that were previously carried out conventionally and the challenges faced by companies in adopting it. This study uses a literature study method to identify trends and findings related to the use of AI in accounting. The results show that AI is able to improve operational efficiency, data analysis, and security, although there are challenges in its implementation, such as human resource adaptation and data security.